Traditional Botanical Knowledge of the Plain Mennonites: Time, change, and knowledge transitions - Brown, Adam; Bridges, Kim; McClatchey, Will (Ethnobotany Research and Applications, 2014)
This study quantifies the culinary and medicinal botanical knowledge of the Old Order or Plain Mennonites in eastern Pennsylvania, a religious group which chooses to reject certain elements of modern technology. The study tests the hypothesis that time, geography, and degree of religious conservatism impact the retention of botanical knowledge. Historical cookbooks and medical texts were combined with data from modern interviews to identify useful plants from a number of locations and times, allowing trends in botanical knowledge to be identified. The dominant pattern presented by these data is one of overall cultural conservatism, and the literate nature of this culture is the best explanatory factor for this pattern.